High Performance Centre Papendal Netherland - Schellens, J. (7. Forum on Elite Sport- INSEP, Paris, France, 28.August.-1. September 2011, 2011)
• 250 athletes training on a daily basis • another 250 athletes training on a regular basis • 150 athletes on full board basis • Athletes from 14 - 40 years old • 17 Olympic and Paralympic Programmes